Therapies currently in Phase II trials for malignant pleural mesothelioma. (October 2013) - Pinton, Giulia; Manente, Arcangela Gabriella; Tavian, Daniela; Moro, Laura; Mutti, Luciano
<x xml:space="preserve">Abstract</x> Introduction: Malignant pleural mesothelioma (MPM) is an aggressive cancer associated with asbestos exposure, whose incidence will peak within the next years. Despite an overall low response rate, the current first-line therapy is represented by combined chemotherapy with cisplatin and antifolate. Moreover, there are no currently approved regimens for relapsed or refractory MPM. Therefore, it is clear how both preclinical and clinical researches aimed at identifying new therapeutic targets and testing them in early clinical settings are badly needed. Areas covered: The aim of this review is to summarize and critically comment the ongoing Phase II trials for MPM. Expert opinion: Over the past few years, there has been a significant endeavor of addressing the clinical research for MPM beyond the very modest results of chemotherapy. Nonetheless, our understanding is that the treatment of MPM should not be merely 'copied' from that of other much better studied tumors. In the light of recent results, studies toward the metabolic characteristics of this tumor are being progressively addressed. These evidences are disclosing a rather unusual model of malignancy, very likely to be more sensitive to novel 'MPM cells- and microenvironment-tailored' therapy addressing these characteristics rather than the sole cancer proliferation.